Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Fowles, Amelia E.; Edgar, Graham J.; Stuart-Smith, Rick D.; Kirkpatrick, James B.; Hill, Nicole; Thomson, Russell J.; Strain, Elisabeth M. A. (Frontiers in Marine Science, 2018)
Expanding urbanisation in estuaries and the increase in pollutants from anthropogenic point sources can affect nearby benthic assemblages. Using a paired impact-control design, we assessed the effects of pollution from anthropogenic point sources (marinas, storm-water drains, sewerage outfalls and fish farms) on algal and sessile invertebrate recruits to pavers placed in an industrialised Tasmanian estuary. Species number and cover of native recruits were lower after 12 months at sites outside marinas relative to paired control sites, whereas non-native and cryptogenic recruits were significantly higher outside marinas and near sewerage outfalls. The cover of fast-growing, opportunistic species was significantly higher at sites near fish farms and sewerage outfalls, and the cover of native species was also greater at sites near sewerage outfalls relative to the paired control sites. Our results suggest an increased management focus on controlling pollution from marinas and sewage outfalls is warranted to limit the spread of non-native and cryptogenic species.